Large-scale impregnation of oceanic and continental slab-derived adakitic melts into the mantle wedge - Pengjie Cai; Jaroslaw Majka; Dongyang Lian; Jingsui Yang; Lu Wang; Haitao Ma; Huichao Rui; Rongzong Bo; Ahmed E. Masoud (Communications Earth & Environment)
Abstract Mantle wedge metasomatism is a widespread phenomenon in subduction zones. However, details of early melt generation and the extent of metasomatic processes is unclear. Here we document two distinct types of adakitic felsic rocks within the mantle wedge of the North Qaidam ultrahigh-pressure metamorphic belt. These field observations provide direct evidence for extensive mantle wedge metasomatism. Zircon and apatite U-Pb dating indicates a rapid exhumation and cooling of the subducted plate. Sr-Nd-Hf isotopic analyses, combined with forward phase equilibrium modeling of partial melting, suggest that these adakitic veins formed either through partial melting of a single continental crustal source or by mixing of melts derived from both oceanic and continental crusts. These findings underscore the critical role of melts derived from both oceanic and continental crusts in the growth and evolution of continental crust during collisional orogenic events.